Migrating to reverse Auction mechanisms in wind energy sector: Status and challenges. (September 2021) - Kandpal, Divik; Dhingra, Tarun
Abstract: India, with a total installed wind power capacity of 39.25 GW, is fourth largest wind producer in the world. The government aims to achieve 60 GW capacity of wind energy by 2022. Accelerated Depreciation (AD) and Generation Based Incentives (GBI) as policy mechanisms supported the initial growth, but the sudden transition to reverse auction mechanism in 2016 brought a big disruption in the market and the regime is yet to be stabilized. Till now 9 tranches of auctions have been conducted by Solar Energy Corporation of India (SECI) and 06 by various states. However, most of the projects allocated through auctions are behind the schedule and many tenders have gone undersubscribed. At present limited literature is available on the status and challenges arisen due to wind energy reverse auctions in India and this paper through systematic literature review does a comprehensive study on the same . Land availability, transmission and evacuation infrastructure bottlenecks, tariff revisions and renegotiation of PPAs by states, poor financial health of state discoms, financing problems, curtailment risk and tariff caps are identified as major challenges faced by wind power developers (WPDs) and these are required to be addressed by the government on priority. Highlights: Identification of the status of wind energy reverse auctions in India. Wind Power Developers challenges due to introduction of reverse auctions. Impact of these challenges on achieving national goal of 60 GW by 2022. Effect of wind energy auctions on the financial position of Wind Power Developers.